2014
DOI: 10.1002/btpr.1994
|View full text |Cite
|
Sign up to set email alerts
|

Toward improving selectivity in affinity chromatography with PEGylated affinity ligands: The performance of PEGylated protein A

Abstract: Chemical modification of macromolecular affinity chromatography ligands with polyethylene glycol chains or "PEGylation" can potentially improve selectivity by sterically suppressing non-specific binding interactions without sacrificing binding capacity. For a commercial protein A affinity media and with yeast extract (YE) and fetal bovine serum (FBS) serving as mock contaminants, we found that the ligand accounted for more than 90% of the media-associated non-specific binding, demonstrating an opportunity for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Despite the great performance of Protein A for purification of mAbs, González‐Valdez et al. demonstrated that the ligand accounted for >90% of the media‐associated non‐specific binding. This finding was evident after testing a commercial Protein A media including yeast extract and fetal bovine serum as contaminants.…”
Section: Protein a Chromatographic Stationary Phasesmentioning
confidence: 99%
“…Despite the great performance of Protein A for purification of mAbs, González‐Valdez et al. demonstrated that the ligand accounted for >90% of the media‐associated non‐specific binding. This finding was evident after testing a commercial Protein A media including yeast extract and fetal bovine serum as contaminants.…”
Section: Protein a Chromatographic Stationary Phasesmentioning
confidence: 99%
“…Protein A contains 55 lysine residues and one N-terminal. It is unclear how many of these are surface residues, but 30 are in the X domain, originally where the protein was covalently bound to the staphylococcal bacteria cell wall [ 18 ]. Azide functionality was introduced into the Protein A structure via NHS ester chemistry involving these lysine groups.…”
Section: Resultsmentioning
confidence: 99%
“…In one of these works, the purification of 20 kDa mono-PEGylated lysozyme with heparin affinity chromatography was optimized through an experimental design [32], and the elution curves for the operation were later simulated [33]. e other studies deal with the PEGylation of ligands in AC supports or resins, with the aim of improving their stability using as model concanavalin and protein A [34,35].…”
Section: Effects Of Pegylation On Protein Affinitymentioning
confidence: 99%